105k views
23 votes
.................................

.................................-example-1

2 Answers

8 votes

Answer:

You have to solve these expressions according to the BODMAS theory.

That is,

B ⇒ Brackets

O ⇒ Of

D ⇒ Division

M ⇒ Multiplication

A ⇒ Addition

S ⇒ Subtraction

Let us verify the expressions now.

a) -5 × [ (-7) + (-5) ] = [ (-5) × (-7) ] + [ (-5) × (-5) ]

-5 × [ -7 -5 ] = [ 35 ] + [ 25 ]

-5 × -12 = 60

60 = 60 (verified)

b) ( -7 ) × [ (-8) + 9 ] = [ -7 × (-8) ] + [ (-7) × 9 ]

-7 × 1 = [ 56 ] - 63

-7 = -7 (verified)

c) (-25) × [ (-7) + (-15) ] = [ (-25) × (-7) ] + [ (-25) × (-15)]

-25 × [ -22 ] = 175 + 375

550 = 550 (verified)

User Alex Reitbort
by
4.5k points
2 votes

For all of these we will use the Order of Operations, also known as PEMDAS, then compare the simplifed values to see if they are equal.

[a] Equivalent / Verified

(-5) * [(-7) + (-5)] = [(-5) * (-7)] + [(-5) * (-5)]

(-5) * [-12] = [35] + [25]

60 = 60

[b] Equivalent / Verified

(-7) * [(-8) + 9] = [-7 * (-8)] + [(-7) * 9]

(-7) * [1] = [56] + [-63]

-7 = -7

[c] Equivalent / Verified

(-25) * [(-7) + (-15)] = [(-25) * (-7)] + [(-25) * (-15)]

(-25) * [-22] = [175] + [375]

550 = 550

.................................-example-1
User John Marter
by
5.3k points